Human capital investments and expectations about career and family - Matthew Wiswall; Basit Zafar (Federal Reserve Bank of New York, 2016)
This paper studies how individuals believe human capital investments will affect their future career and family life. We conducted a survey of high-ability currently enrolled college students and elicited beliefs about how their choice of college major, and whether to complete their degree at all, would affect a wide array of future events, including future earnings, employment, marriage prospects, potential spousal characteristics, and fertility. We find that students perceive large 'returns" to human capital not only in their own future earnings, but also in a number of other dimensions (such as future labor supply and potential spouse's earnings). In a recent follow-up survey conducted six years after the initial data collection, we find a close connection between the expectations and current realizations. Finally, we show that both the career and family expectations help explain human capital choices.
Keywords: D81; D84; I21; I23; J10; J12; J13; J16; J24; 330; human capital; subjective expectations; college major; uncertainty; marriage; fertility; labor supply; gender